Acute effect of carbamazepine on corticothalamic 5–9‐Hz and thalamocortical spindle (10–16‐Hz) oscillations in the rat. (6th December 2013) - Zheng, Thomas W.; O'Brien, Terence J.; Kulikova, Sofya P.; Reid, Christopher A.; Morris, Margaret J.; Pinault, Didier
Abstract A major side effect of carbamazepine (CBZ), a drug used to treat neurological and neuropsychiatric disorders, is drowsiness, a state characterized by increased slow‐wave oscillations with the emergence of sleep spindles in the electroencephalogram (EEG). We conducted cortical EEG and thalamic cellular recordings in freely moving or lightly anesthetized rats to explore the impact of CBZ within the intact corticothalamic (CT)–thalamocortical (TC) network, more specifically on CT 5–9‐Hz and TC spindle (10–16‐Hz) oscillations. Two to three successive 5–9‐Hz waves were followed by a spindle in the cortical EEG. A single systemic injection of CBZ (20 mg/kg) induced a significant increase in the power of EEG 5–9‐Hz oscillations and spindles. Intracellular recordings of glutamatergic TC neurons revealed 5–9‐Hz depolarizing wave–hyperpolarizing wave sequences prolonged by robust, rhythmic spindle‐frequency hyperpolarizing waves. This hybrid sequence occurred during a slow hyperpolarizing trough, and was at least 10 times more frequent under the CBZ condition than under the control condition. The hyperpolarizing waves reversed at approximately −70 mV, and became depolarizing when recorded with KCl‐filled intracellular micropipettes, indicating that they were GABAA receptor‐mediated potentials. In neurons of the GABAergic thalamic reticular nucleus, the principal source of TC GABAergic inputs, CBZ augmented both the number and the duration of sequences of rhythmic spindle‐frequency bursts of action potentials. This indicates that these GABAergic neurons are responsible for the generation of at least the spindle‐frequency hyperpolarizing waves in TC neurons. In conclusion, CBZ potentiates GABAA receptor‐mediated TC spindle oscillations. Furthermore, we propose that CT 5–9‐Hz waves can trigger TC spindles.